Modulation of lignin biosynthesis for drought tolerance in plants - Choi, Su Jeong; Lee, Zion; Kim, Sohyun; Jeong, Eui; Shim, Jae Sung (Frontiers in Plant Science, 2023)
Lignin is a complex polymer that is embedded in plant cell walls to provide physical support and water protection. For these reasons, the production of lignin is closely linked with plant adaptation to terrestrial regions. In response to developmental cues and external environmental conditions, plants use an elaborate regulatory network to determine the timing and location of lignin biosynthesis. In this review, we summarize the canonical lignin biosynthetic pathway and transcriptional regulatory network of lignin biosynthesis, consisting of NAC and MYB transcription factors, to explain how plants regulate lignin deposition under drought stress. Moreover, we discuss how the transcriptional network can be applied to the development of drought tolerant plants.